2022
DOI: 10.3174/ajnr.a7475
|View full text |Cite
|
Sign up to set email alerts
|

Third Trimester Structural and Diffusion Brain Imaging after Single Intrauterine Fetal Death in Monochorionic Twins: MRI-Based Cohort Study

Abstract: BACKGROUND AND PURPOSE: Single intrauterine fetal death increases the risk of antenatal brain lesions in the surviving twin. We evaluated the prevalence of structural brain lesions, biometry, and diffusivity on routine third trimester MR imaging performed following single intrauterine fetal death. MATERIALS AND METHODS:In a retrospective MR imaging-based cohort study, we compared 29 monochorionic twins complicated with single intrauterine fetal death (14 following laser ablation treatment for twin-to-twin tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Twelve out of twenty-three studies described fetal MRI findings in surviving MC co-twins after sIUFD [8,13,14,16,23,25,26,[28][29][30]. This resulted in the second largest group studied with fetal MRI, with brain imaging findings reported in 862 fetuses.…”
Section: Single Intrauterine Fetal Demisementioning
confidence: 99%
See 4 more Smart Citations
“…Twelve out of twenty-three studies described fetal MRI findings in surviving MC co-twins after sIUFD [8,13,14,16,23,25,26,[28][29][30]. This resulted in the second largest group studied with fetal MRI, with brain imaging findings reported in 862 fetuses.…”
Section: Single Intrauterine Fetal Demisementioning
confidence: 99%
“…Of note, in 111 cases, sIUFD was caused by selective fetal reduction. The studies reported a median overall incidence of cerebral injury in single survivors of 28.3% (range 0-55%) after sIUFD [8,13,14,16,17,23,25,26,[28][29][30]. We made a distinction between studies with single survivors after selective fetal reduction and other causes of sIUFD because of the different mechanisms of cerebral injury.…”
Section: Single Intrauterine Fetal Demisementioning
confidence: 99%
See 3 more Smart Citations